ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY OF LEUCAS ASPERA FLOWERS FROM BIHAR, INDIA. - Sabri, Gulnaaz; Y, Vimala (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of this study was to explicate antibacterial, antifungal, and antioxidant activities of Leucas aspera flowers. Methods: Antibacterial activity was done by agar diffusion method. The ethyl acetate extract of L. aspera flower was evaluated against both Gram-positive and Gram-negative bacteria. Antifungal activity was also done by agar diffusion method. The agar used for antifungal activity was Czapek Dox Agar. Nitric oxide scavenging assay and free radical scavenging assay were used for the antioxidant activity. Griess reagent was used in nitric oxide scavenging assay. 1,1-diphenyl-2-picryl hydrazyl was used in free radical scavenging assay. Results: L. aspera flower extract showed good antibacterial activity with the highest zone of inhibition against Vibrio cholera with 23 mm followed by Bacillus polymyxa showing 20 mm zone of inhibition. The ethyl acetate extract of L. aspera flower showed quite a good results with the highest inhibitory activity against Aspergillus niger with 13 mm zone of inhibition and lowest for Trichoderma viridae with 5 mm zone of inhibition. Antioxidant activity of L. aspera flower extract was done by free radical scavenging assay and nitric oxide scavenging assay. Nitric oxide scavenging assay showed prominent results almost performed equal to standard compound Butylated hydroxyl anisole (BHA) The values for 10 Î¼l of L. aspera extract was 50.27, for the standard (BHA) showed 50.81. L. aspera extract values for 50 Î¼l was 69.73 and for BHA, the values was 77.30. For 100 Î¼l, the extract gave 82.70, and for standard BHA, the reading was 89.73. Conclusion: The results showed that L. aspera flower has broad-spectrum antibacterial activity ranging from 23 to 13 mm zone of inhibition. L. aspera flower has strong antioxidative power on nitric oxide radicals. The medicinal properties of plant species have made an outstanding contribution to the origin and evolution of many traditional herbal therapies.